2019
DOI: 10.21522/tijpy.2016.04.01.art002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey to Assess the Prevalence and Consequences of Domestic Violence among Married Women in Zage, Kano, Nigeria

Abstract: Background: Domestic Violence refers to violence emanating from the household and within relationships defined by familial or emotional (former or present) attachment. It is the most common form of violence against women and affects women across the life span, from sex-selective abortion of female fetuses to forced suicide and abuse of older women. Domestic violence is evident to some degree in every society in the world. The main objective of the study was to assess the prevalence and consequences of domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…Women who use at least one substance were 3.4 times more likely to be victims of intimate partner violence than those who do not use substances. This finding is in line with studies conducted in Ethiopia ( 29 , 32 ). This is similar with the effects of alcohol consumption mentioned above,.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women who use at least one substance were 3.4 times more likely to be victims of intimate partner violence than those who do not use substances. This finding is in line with studies conducted in Ethiopia ( 29 , 32 ). This is similar with the effects of alcohol consumption mentioned above,.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with the findings of different studies conducted in Ethiopia (47%) ( 28 ) (51.7%) ( 29 ), (48.6%) ( 30 ), in Bangladeshi (53%) ( 31 ), and in Nigeria (50%) ( 32 ). On the other hand, this finding is higher than studies conducted in Ethiopia (32.5%) ( 11 ), (19.6%) ( 33 ) in sub-Saharan Africa (35.5%) ( 34 ), in Nigeria (29%) ( 35 ), in the Republic of Cyprus ( 8 , 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Violence by intimate partners has been identified as a major cause of injury to women4. Different studies demonstrate that physical and sexual abuse of women has resulted in a wide range of negative health outcomes, such as gynecological disorders, HIV/AIDS, unwanted pregnancy, abortion, still birth, gastrointestinal disorders, chronic pain syndromes, and mental health disorders (Ellsberg et al, 2008, Loxton et al, 2006, Plichta and Falik, 2001, Romito et al, 2005. A study conducted among rape victims attending a hospital in Adigrat town, Ethiopia, found that physical and genital injuries, sexual and psychiatric problems were the common consequences of rape (Gessessew and Mesfin, 2004).…”
Section: Background Of the Studymentioning
confidence: 99%